Core expansion of bis-calix[4]arene-supported clusters. Issue 99 (22nd November 2016) - Coletta, Marco; McLellan, Ross; Waddington, Amy; Sanz, Sergio; Gagnon, Kevin J.; Teat, Simon J.; Brechin, Euan K.; Dalgarno, Scott J.
Abstract : Stoichiometric control allows for remarkable expansion of the cores of two known bis-calix[4]arene-supported clusters, with concomitant changes to the magnetic properties. Abstract : Calix[4]arenes are excellent ligand supports for the synthesis of polymetallic clusters of transition and lanthanide metal ions, as well as 3d–4f ion mixtures. Bis-calix[4]arene, a recent addition to the calixarene family, forms structurally related cages that mirror the metal ion binding preferences of calix[4]arene. Here we show that stoichiometric control causes remarkable expansion in the cores of two known bis-calix[4]arene-supported clusters, with concomitant changes to the magnetic properties observed.